Effects of Formalin Fixation on Myelin Water Fraction MRI Measurements in Human White Matter: a Novel Ex Vivo Study - Shatil, Anwar S.; Matsuda, Kant M.; Figley, Chase R. (CMBES Proceedings, 2017)
No Abstract